The TF:VIIa Complex: Clinical Significance, Structure-function Relationships and Its Role in Signaling and Metastasis - Konigsberg, William; Kirchhofer, Daniel; Riederer, Markus A.; Nemerson, Yale (Thrombosis and Haemostasis, 2001)
In healthy humans, blood vessel-tissue factor is found primarily in the adventitia and thus physically separated from coagulation factors, which mainly circulate in an inactive form. Following injury, TF is exposed to blood and initiates the coagulation cascade. The resulting fibrin formation is an essential part for the initial repair of vessel damage to minimize blood-loss (reviewed by (1-4). Therefore, TF may be considered to form a hemostatic sheath around blood vessels essential for hemostasis and appears to be essential for life inasmuch as no TF deficiency has been reported and TF knockout mice do not survive beyond the perinatal period.